1990
DOI: 10.1161/01.str.21.9.1306
|View full text |Cite
|
Sign up to set email alerts
|

A simple test to assess cerebrovascular reserve capacity using transcranial Doppler sonography and acetazolamide.

Abstract: The goal of this study was the development of a simple bedside test to assess cerebrovascular reserve capacity using transcranial Doppler sonography. We studied 33 normal persons at rest and after stimulation of cerebral blood flow with 1 g acetazolamide. Their mean±SD increase in blood flow velocity in 54 middle cerebral arteries 10 minutes after stimulation was 24.4 ±9.2 cm/sec. We tried to validate the increase in blood flow velocity as cerebrovascular reserve capacity in 21 patients with obstructive caroti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
108
2
8

Year Published

1992
1992
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(126 citation statements)
references
References 29 publications
8
108
2
8
Order By: Relevance
“…When using asymmetry in increase and a lower limit, there was only one false-positive finding with TCD when SPECT was used as the reference method, but 11 hemispheres with moderate changes were not detected with TCD. Piepgras et al 16 compared TCD and SPECT findings when vasoreactivity was assessed with acetazolamide in 21 patients with carotid occlusive diseases. They found one falsepositive and six false-negative detections of reduced vasoreactivity with TCD when SPECT was used as the reference method.…”
Section: Discussionmentioning
confidence: 99%
“…When using asymmetry in increase and a lower limit, there was only one false-positive finding with TCD when SPECT was used as the reference method, but 11 hemispheres with moderate changes were not detected with TCD. Piepgras et al 16 compared TCD and SPECT findings when vasoreactivity was assessed with acetazolamide in 21 patients with carotid occlusive diseases. They found one falsepositive and six false-negative detections of reduced vasoreactivity with TCD when SPECT was used as the reference method.…”
Section: Discussionmentioning
confidence: 99%
“…This procedure is widely used as a simple and reliable tool to test vasomotor reactivity of the cerebral microvasculature. 6,7 In this study, the test was performed in identical fashion between 8:00 and 10:00 AM before and after a 2-month treatment with pravastatin sodium 20 mg daily. Additional potentially vasoactive medication such as antihypertensives remained unchanged during the study period.…”
Section: Methodsmentioning
confidence: 99%
“…The mean cerebral blood flow velocity (CBFV mean ) was calculated from the envelope curve of the velocity spectrum during rest and 5 minutes after bolus injection of 1 g acetazolamide over an averaging period of 5 minutes each. Relative CBFV mean changes were calcu- 6,7 In this study, the test was performed in identical fashion between 8:00 and 10:00 AM before and after a 2-month treatment with pravastatin sodium 20 mg daily. Additional potentially vasoactive medication such as antihypertensives remained unchanged during the study period.…”
mentioning
confidence: 99%
“…Most common side effects are acute and transient, including transient circumoral numbness, paresthesias, malaise, and headache. 23,24 Reversible pontine ischemia caused by ACZ challenge has been discussed in a case report 25 ; however, Piepgras et al 26 reported no acute ischemic sequelae in more than 1000 studies with the use of ACZ.…”
mentioning
confidence: 99%